ANALISIS RASIO LIKUIDITAS PADA PT BANK PAN INDONESIA ,TBK PERIODE 2018-2022 - Sunly Amalia Tsamara (2023)
This study aims to determine the company's financial performance by using liquidity ratio analysis. The liquidity ratios used include LDR (Loan to Deposit Ratio), Current Asset Ratio, and Cash Ratio. The method of writing this final project uses a quantitative method in the form of secondary data, namely the financial statements of PT. Bank Pan Indonesia, Tbk for the 2018-2022 period. LDR (Loan to Deposit Ratio) uses the results of a comparison between loans and third party funds. The current ratio uses the results of a comparison between current assets and current liabilities. The Cash Ratio uses the results of a comparison between cash and cash equivalents with current liabilities. From this study, the average results of the LDR (Loan to Deposit Ratio) ratio are still in the criteria of being quite healthy, the current ratio is in the criteria of being healthy, and the Cash Ratio is in the criteria of being very healthy.